The floating signifier of "safety": correctional officer perspectives on COVID-19 restrictuions, legitimacy and prison order - Schultz, William; Ricciardelli, Rosemary (My University, 2022)
The COVID-19 pandemic continues to affect prisons internationally. Existing research focuses on infections data, meaning we do not fully understand how COVID-19 shapes front-line prison dynamics. We draw on qualitative interviews with 21 Canadian federal correctional officers, exploring how the pandemic impacted prison management. Officers suggested inconsistent messaging around COVID-19 protocols reduced institutional and officers’ self-legitimacy, fracturing trust relationships with incarcerated people. Furthermore, officers suggest that personal protective equipment (PPE) such as gowns and face shields took on multiple meanings. We use Lévi-Strauss’ floating signifier concept to analyze how individual definitions of “safety” informed day-to-day prison routines. We conclude by arguing that legitimacy deficits and contested definitions of “safety” will continue to create uncertainty, impacting prison operations going forward.
Keywords: COVID-19; prison; correctional officers; legitimacy; decision-making